Comparison of conventional doxorubicin with liposome encapsulated doxorubicin as a treatment of breast cancer-a review - Akter, Honufa (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.